Deutschland Unsere Mutter, Columbia Our Bride: German-America in the Progressive Era - Taylor Holmes (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2013)
In many histories of American involvement in the First World War, the anti-German hysteria that exploded in the United States is often trivially attributed to the reality that America had declared war on Germany and the consequent propaganda the war effort generated. This, however, overlooks the significant presence of anti-German sentiment prior both to the outbreak of the First World War and American entry into the war. Precedent to and coincident with U.S. military intervention in Europe was the domestic cultural struggle between an ascendant and dominantly Anglo-American Progressive ideology and a cultural pluralism that German-American ethnic pride embodied. The First World War provoked these latent tensions into active violence. Through the use of secondary sources, this study analyzes the underlying motivations of anti-German prejudice and the driving ideologies behind Anglo-American cultural chauvinists and German-American ethnic pride. The waning of German ethnic institutions in America is likewise examined, as is the growth and decline of the National German-American Alliance. This study is not only a contribution to the relatively small amount of research completed on the history of German-American communities, but is also an addition to the histories of the Progressive Era as it analyzes the goal of Progressive ideology to produce conformity to a homogeneous “American” culture and its resulting manifestations of racism and prejudice.
Keywords: Germany; Culture; Immigration